(untitled) (Journal of Plant Disease Sciences, 2020)
The present study was concerned with the formulation of suitable culture media for growth of non-symbiotic nitrogen fixing, phosphate soulbilizing and potash mobilizing bacteria in a consortium. Among the different culture media, BIO-MS VII media having Glucose (10 g/L), Ammonium sulphate (0.1 g/L) Yeast extract (1 g/L), Tri calcium phosphate (4 g/L) and Calcium carbonate, Calcium phosphate, Potassium aluminum silicates, K2HPO4 1.75 g/L each recorded maximum growth and cfu count of Azotobacter chroococcum, phosphate soulbilizing and potash mobilizing bacteria. These three beneficial microorganisms found to be compatible with each other when grown on BIO-MS VII culture media.